1988
DOI: 10.1128/aac.32.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ciprofloxacin on theophylline clearance and steady-state concentrations in serum

Abstract: The effect of a multiple-dose regimen of oral ciprofloxacin (750 mg every 12 h for 11 doses) on the clearance and steady-state concentrations of theophylline in trough (predose) serum was evaluated in nine healthy male subjects, each serving as his own control. Theophylline was taken as a sustained release tablet per os in a dose of 200 mg every 12 h for 19 doses. Theophylline concentrations in serum were measured immediately before each theophylline dose. Ciprofloxacin was administered on study day 4 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 8 publications
5
33
0
1
Order By: Relevance
“…Ciprofloxacin is a potent inhibitor of CYP1A2 and a weak inhibitor of CYP3A4 [4,5] . Some npg studies have demonstrated a drug-drug interaction when ciprofloxacin was co-administered with other drugs, including theophylline [6,7] , caffeine [8] , clozapine [9] , methadone [10] and zolpidem [11] . Ciprofloxacin is commonly prescribed with analgesics for the management of infection, pain and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin is a potent inhibitor of CYP1A2 and a weak inhibitor of CYP3A4 [4,5] . Some npg studies have demonstrated a drug-drug interaction when ciprofloxacin was co-administered with other drugs, including theophylline [6,7] , caffeine [8] , clozapine [9] , methadone [10] and zolpidem [11] . Ciprofloxacin is commonly prescribed with analgesics for the management of infection, pain and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…i. The mean pharmacokinetic parameters are provided in Table 1. DISCUSSION Enoxacin was the first new fluoroquinolone noted to decrease theophylline clearance (2,15,16 (10,13,16). However, a decrease in theophylline clearance up to 65% was well documented in a patient receiving ciprofloxacin and theophylline (14).…”
Section: Methodsmentioning
confidence: 99%
“…Rarely, hallucinations, delirium, and seizures have occurred, predominantly in patients who also were receiving theophylline or a nonsteroidal antiinflammatory drug. Ciprofloxacin and pefloxacin inhibit the metabolism of theophylline, and toxicity from elevated concentrations of the methylxanthine may occur [51]. Nonsteroidal antiinflammatory drugs may augment displacement of g-aminobutyric acid (GABA) from its receptors by the quinolones [52].…”
Section: Adverse Effectsmentioning
confidence: 99%